PENAKERJA: GERAKAN ECOSCHOOL PADA SEKOLAH-SEKOLAH MUHAMMADIYAH DI PCM KARTASURA, SUKOHARJO - Susilawati, Siti Azizah; Sunarhadi, Muhammad Amin; Priyono, Kuswaji Dwi; Indrawati, Indrawati; Nurhasan, Nurhasan (Universitas Muhammadiyah Surakarta, 2015)
School as an institution where children get education, teaching and learning so that the school produced a superior human beings and qualified. Kartasura PCM is one of the flagship PCM in PDM Sukoharjo have elementary school level that has been known in the community, namely: MIM PK Muhammadiyah Kartasura, MIM Pucangan, Kertonatan MIM, MIM Gonilan and SDIT Al Kawthar Makamhaji Kartasura. The current fifth that grade school has a good reputation in the community. This community service aimed to increased awareness of the environment from all components of school at Muhammadiyah Elementary schools in PCM Kartasura. The first stage wasthe policy workshop school by school leaders and teachers, the second was distribute the grant of trash cans and posters, the third stage wasparticipatory education of Hole Infiltration Biopori and the fourth stage was monitoring. Monitoring results found that posters used as it should be, but the trash cans are still not being used properly, placement of trash cans were not side by side and still foundedthe organic waste mix with an organic waste in the same trash cans. This community service is an initial step the realization of school basedeco-school